A pragmatic approach to intravenous anaesthetics and electroencephalographic endpoints for the treatment of refractory and super-refractory status epilepticus in critical care. (February 2020) - Prisco, Lara; Ganau, Mario; Aurangzeb, Sidra; Moswela, Olivia; Hallett, Claire; Raby, Simon; Fitzgibbon, Karina; Kearns, Christopher; Sen, Arjune
Abstract: Status epilepticus is a common neurological emergency, with overall mortality around 20%. Over half of cases are first time presentations of seizures. The pathological process by which spontaneous seizures are generated arises from an imbalance in excitatory and inhibitory neuronal networks, which if unchecked, can result in alterations in intracellular signalling pathways and electrolyte shifts, which bring about changes in the blood brain barrier, neuronal cell death and eventually cerebral atrophy. This narrative review focusses on the treatment of status epilepticus in adults. Anaesthetic agents interrupt neuronal activity by enhancing inhibitory or decreasing excitatory transmission, primarily via GABA and NMDA receptors. Intravenous anaesthetic agents are commonly used as second or third line drugs in the treatment of refractory status epilepticus, but the optimal timing and choice of anaesthetic drug has not yet been established by high quality evidence. Titration of antiepileptic and anaesthetic drugs in critically ill patients presents a particular challenge, due to alterations in drug absorbtion and metabolism as well as changes in drug distrubution, which arise from fluid shifts and altered protein binding. Furthermore, side effects associated with prolonged infusions of anaesthetic drugs can lead to multi-organ dysfunction and a need for critical care support. Electroencelography can identify patterns of burst suppression, which may be a target to guide weaning of intravenous therapy. Continuous elctroencephalography has the potential to directly impact clinical care, but despite its utility, major barriers exist which have limited its widespread use in clinical practice. A flow chart outlining the timing and dosage of anaesthetic agents used at our institution is provided.